2015
DOI: 10.1080/01916122.2015.1052154
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation and pollen along a 200-km transect in Khyber Pakhtunkhwa Province, northwestern Pakistan

Abstract: This paper presents the first study on the relationship between vegetation and modern pollen rain along a 200-km elevational gradient (275À2600 m above sea level), in the Khyber Pakhtunkhwa Province of northwestern Pakistan. A vegetation survey of 24 plots (six plots of 10 £ 10 m from four elevational zones) was carried out following the Braun-Blanquet method. The percentage cover of all taxa was documented and species were assigned to their respective families. Twenty-four surface samples (taken from the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…3) shows the pollen taxa assigned to the different vegetation groups. Our published study of a pollen rain transect of this area (Jan et al 2015) indicated that the source of the pollen is local (originating from vegetation on a 5 km 2 mountain area around the coring site) and represented predominantly by Pinus, Picea, Cedrus, Abies, Cyperaceae and Poaceae species.…”
Section: Pollen Diagrammentioning
confidence: 96%
See 1 more Smart Citation
“…3) shows the pollen taxa assigned to the different vegetation groups. Our published study of a pollen rain transect of this area (Jan et al 2015) indicated that the source of the pollen is local (originating from vegetation on a 5 km 2 mountain area around the coring site) and represented predominantly by Pinus, Picea, Cedrus, Abies, Cyperaceae and Poaceae species.…”
Section: Pollen Diagrammentioning
confidence: 96%
“…At present, the conifers on the surrounding mid-altitude mountains (1500-3000 m a.s.l) include Pinus and Picea species, while the high-altitude mountains (3000-5000 m a.s.l.) have Cedrus species (Jan et al 2015, Siddiqui et al 1999). An important task is to trace the history and temporal dynamics of these conifers on the surrounding Hindu Kush mountains of the Swat Valley.…”
mentioning
confidence: 99%
“…3) shows pollen taxa assigned to the different vegetation groups such as conifers, Trees/Shrubs and herbs. Our published paper on the pollen rain transect study of this area reveals that the source of the pollen is local, originating in the surrounding mountain vegetation with Pinus, Picea, Cedrus, Abies, Cyperaceae and Poaceae species (Jan et al, 2015). 115…”
Section: Pollen Diagrammentioning
confidence: 96%
“…Natural coniferous forests of Pinus, Abies, Cedrus and Picea are also under the heavy social and economic pressure of logging . Our paper dealing with vegetation and modern pollen rain in Kabal Swat (Jan et al, 2015)…”
Section: Vegetationmentioning
confidence: 99%